STRATEGI DIPLOMASI PUBLIK KOREA SELATAN DI ASIA TENGGARA SEBAGAI NEGARA MIDDLE POWER - , I GUSTI AYU AZARINE K.A.; , Dr. Poppy S. Winanti, MPP, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The term and idea of middle power has often been discussed in international relations contexts after the Cold War. Middle power countries are mostly countries who were neither big or small in terms of economy, size, population, and most importantly, influence in the global politic. Middle power countries diplomacy is called middlepowermanship and it is distinguishable from traditional diplomacy in which this type of diplomacy is to exercise influence and take international initiative through international co-operation and regimes in contemporary issues. Middlepowermanship are often actualized through public diplomay which became the one foremost characteristic of a middle power. South Korea is a latecomer to middle power diplomacy, which used to be dominated by a few conventional and rising middle powers. Eventhough South Korea has maintained a strong identity as a middle power particularly due to itsâ abundant resources in soft power however South Korea hadnât translated itsâ power to a middle power diplomacy until the inauguration of the Lee Myung Bak administration in 2008. Under the slogan of Global Korea, Lee Myung Bak employed proactive diplomacy through an implementation of public diplomacy in order to craft a strong middle power identity which was characterized with active contributions to international community through a cooperation. This thesis aims to explore about South Koreaâs public identity as a middle power and itsâ foreign policy as a middle power which was translated into a public diplomacy efforts in Lee Myung Bak administration. The thesis also aims to unfolded more research in the contexts of middle power and itsâ distinguishable foreign policy which was based not on overwhelming national powers but rather a soft powers.